The neuroendocrine sequelae of paediatric craniopharyngioma: a 40-year meta-data analysis of 185 cases from three UK centres. Issue 3 (March 2017) - Tan, Timothy Shao Ern; Patel, Leena; Gopal-Kothandapani, Jaya Sujatha; Ehtisham, Sarah; Ikazoboh, Esieza Clare; Hayward, Richard; Aquilina, Kristian; Skae, Mars; Thorp, Nicky; Pizer, Barry; Didi, Mohammed; Mallucci, Conor; et al.
Abstract : Objectives: The management of paediatric craniopharyngiomas was traditionally complete resection (CR), with better reported tumour control compared to that by partial resection (PR) or limited surgery (LS). The subsequent shift towards hypothalamic sparing, conservative surgery with adjuvant radiotherapy (RT) to any residual tumour aimed at reducing neuroendocrine morbidity, has not been systematically studied. Hence, we reviewed the sequelae of differing management strategies in paediatric craniopharyngioma across three UK tertiary centres over four decades. Methods: Meta-data was retrospectively reviewed over two periods before (1973–2000 (Group A: n  = 100)) and after (1998–2011 (Group B: n  = 85)) the introduction of the conservative strategy at each centre. Results: Patients had CR (A: 34% and B: 19%), PR (A: 48% and B: 46%) or LS (A: 16% and B: 34%), with trends reflecting the change in surgical approach over time. Overall recurrence rates between the two periods did not change (A: 38% vs B: 32%). More patients received RT in B than A, but recurrence rates were similar: for A, 28% patients received RT with 9 recurrences (32%); for B, 62% received RT with 14 recurrences (26%). However, rates of diabetes insipidus ( P  = 0.04), gonadotrophin deficiency ( P  < 0.001) and panhypopituitarism ( P  = 0.001) were lower in B than those in A. In contrast, post-operative obesity (BMI SDS >+2.0) ( P  = 0.4) and hypothalamic ( P  = 0.1) and visual ( P  = 0.3) morbidity rates were unchanged. Conclusion: The shift towards more conservative surgery has reduced the prevalence of hormone deficiencies, including diabetes insipidus, which can be life threatening. However, it has not been associated with reduced hypothalamic and visual morbidities, which remain a significant challenge. More effective targeted therapies are necessary to improve outcomes.